Insurance experience as a category of labor law and social security law - Вишновецька, Світлана Василівна; Григолінський, Сергій Олексійович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
The article investigates insurance experience as a category of labor law and social security law. Defined as the period specified concept, process, legal fact and inter-Law Institute, and the main features of insurance, the insurance value is set and seniority.